Kinetic profiles of the stereoselective reduction of acetophenone and its derivatives promoted by Galactomyces candidus GZ1. A mechanistic interpretation - Decarlini, Maria Florencia (2019)
A mechanistic interpretation of the kinetic profiles obtained for the stereoselective reduction of acetophenone promoted by Galactomyces candidus GZ1 under aerobic and anaerobic conditions was made. Based on experimental and bibliographical data, a mechanism which may involve the participation of two alcohol dehydrogenases with opposite stereoselectivities and alcohol oxidase is discussed. Due to the stereoselectivity of the reduction of acetophenone being changed when anaerobic conditions were used, this microorganism also permitted (S)-1-phenylethanol to be obtained in the absence of oxygen. Moreover, the kinetic profiles of the reactions of a racemic mixture of (R,S)-1-phenylethanol and pure (S)-1-phenylethanol with Gal. candidus were analyzed, which corroborated that there existed a reaction step where (S)-1-phenylethanol was oxidized to acetophenone. The results presented here show that not only is it possible to resolve racemic mixtures of phenylethanols when Gal. candidus is used as a biocatalyst, but that this is also efficient in causing the complete stereoinversion of pure (S)-1-phenylethanol to (R)-1-phenylethanol.